Muslim powerlessness and the Nation-state - Saleem, Muhammad Yusuf (International Islamic University Malaysia, 2004)
Allah s.w.t in order to save communities from injustice makes them to check and counter each other. This mutual checking produces the necessary balance and equilibrium that enable human societies to live in peace and tranquillity. When the Muslim Ummah was powerful it provided the required check over other communities that consequently brought about justice and order to human societies. However, with the decline of Muslims they are no longer able to check other communities and to defend themselves. There are many factors responsible for the powerlessness of the Muslim world. This paper, however, focuses on the composition of the Muslim nation-state and its consequences. It argues that the present treatment of ethnic, cultural, and lingual diversities within the Muslim nation-state is the source of many problems that confront the Muslim world. The paper argues for the recognition of ethnic, lingual, and cultural diversities within the Muslim nation-state. It suggests that institutions be established to investigate conflicts that may arise from the composition of the Muslim nation-state. The policy of accommodation may, to a greater extent, eliminate the sources of conflicts within the Muslim nation-state and among the Muslin nation-states. This subsequently may bring about a degree of unity to the Muslim world that would enable them to check and counter other communities.